Prevalence of dermatological conditions in tribal place of Timbi, Bhavnagar (Saurashtra) - Shah, Bhuvnesh Girish; Sheth, Keya Jayesh (International Journal of Research in Dermatology, 2017)
Background: Skin is one of the major organs of our body. With time people have started taking due care of their skin. Also with changing civilization, there are new problems up springing every now and then. Even prevalence of skin diseases is different from place to place. No precise data is available to know the exact occurrence of dermatological conditions in Timbi. Hence a study was undertaken to know the burden of the disease in that area. Methods: A study of 9500 cases, was undertaking in tribal area of Timbi. Males and females were included in the study. Results: It was observed that occupation and the literacy level has somewhat co-relation with the nature, occurrence, and pattern of disease that was seen. Also it was noted that skin diseases were directly or indirectly related to systemic diseases. It was observed that once the systemic diseases were treated, the skin condition improved drastically. Also it brought into the limelight, the nuisance of irrational and improper usage of steroid. As per our observation, half of the complications seen were due to steroids. Majority cases were of Tinea, along with eczema and psoriasis. Cases like pellagroid dermatitis were also seen along with zinc dermatitis. Conclusions: This study was helpful in understanding the nature of diseases which prevailed, helped in planning of an effective healthcare system and also brought into the notice how commonly the steroids are being used for irrational case. Also it helped in emphasizing the need of educating people and creating awareness amongst them.